AKHMAD TASHKUPRIZADA’S CONCEPTION OF ETHICS - Ergashev Urolbek Berkinovich (The Conference Hub, 2025)
The ideas put forward in the moral views of the famous scientist and encyclopedist of the 16th century Akhmad Tashkuprizada are relevant today. His ideas in the first place are filled with humanism and the human factor. The ideas of Tashkuprizada in the conditions of independence of our country can serve the prosperity of justice, science, enlightenment, the study of professions and the spiritual and moral development of society. This article shows more detailed information.
Keywords: Tashkuprizada, science, discussion ethics, diet, commercial ethics, ethics of wealth accumulation.